(3QSGdI GdJfRjg Edi LeGYI GdehMOjfs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj,J (B433 (3g` s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe GdYdi HSe Gddg GdQMef GdQMje OYGI YHOg GdEeGe ef YHO YQa ehdGfG ai GdXghQ hGdcJeGf s
(3BNQgG (B:s
(3efRg Yf MOhO GdOjf hGdOfjG dGjONd ai GdGhgGe hGdNhGWQ SHMGfg hJYGdi YeG jUahf hGdMeO hGdTcQ dg hMOg hgh MSHfG hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3QSGdI ef QSGFd GdOQhRs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B79s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds